INSTITUTIONAL PSYCHOPEDAGOGY: : WHAT IS THIS PROFESSIONAL AND WHAT DOES HE DO? - Rodrigues Linhares Farias, Jacqueline; Maria Pereira Ribeiro Santos, Janaina (Revista Gênero e Interdisciplinaridade, 2021)
The discussion of this text arose due to an elective course in the Psychopedagogy course, we realized that it was necessary to understand who the Institutional Psychopedagogy was. But before that, we would also need to understand a little bit about Psychopedagogy, how it emerged in Brazil, what Institutional Psychopedagogy does and where it is possible to act. We seek bibliographical basis in order to contribute to the recognition of the Psychopedagogy profession in Institutions and to discuss a little about its progressive and effective contribution.